Becoming urban: How city life shapes the social structure and genetics of ants. Issue 18 (25th August 2022) - Janda, Milan
Abstract : Cities and urban environments can do peculiar things to biodiversity that shares them with us. How cities affect their invited and uninvited inhabitants has become an increasingly important question. More than half of the world's population dwells in urban areas, and these environments will keep expanding considerably. Understanding how this relatively recent, rapid, and pervasive form of landscape modification influences the ecology and evolution of organisms that cannot escape, or may benefit from it, is an emerging field of biology. Although we are aware of how some birds, mammals or plants respond to urban environments, less is known about insects and invertebrates in general. In this issue of Molecular Ecology, Blumenfeld et al. (2022) bring new remarkable insights into how a common ant species adjusts to urban settings across the United States by changing its social structure and behaviour. Using a large‐scale molecular, chemical and behavioural dataset, they document how the odorous house ant Tapinoma sessile differs in its colony organisation and dispersal strategy between rural and urban habitats. In each of the study regions and continent‐wide, rural and urban colonies are genetically and chemically differentiated, suggesting that urban settings act as potent agents of selection and isolation. The novelty and importance of this study are that it documents multiple independent transitions toward the same social organisation and the apparent effect of habitat on the life history of a eusocial insect species.